Elucidation of the Charging Mechanisms and the Coupled Structural–Mechanical Behavior of Ti3C2Tx (MXenes) Electrodes by In Situ Techniques. Issue 8 (3rd January 2023) - Bergman, Gil; Ballas, Elad; Gao, Qiang; Nimkar, Amey; Gavriel, Bar; Levi, Mikhael D.; Sharon, Daniel; Malchik, Fyodor; Wang, Xuehang; Shpigel, Netanel; Mandler, Daniel; Aurbach, Doron
Abstract: The discovery of the Ti3 C2 T x compounds (MXenes) a decade ago opened new research directions and valuable opportunities for high‐rate energy storage applications. The unique ability of the MXenes to host various mono‐ and multivalent cations and their high stability in different electrolyte environments including aqueous, organic, and ionic liquid solutions, promoted the rapid development of advanced MXene‐based electrodes for a large variety of applications. Unlike the vast majority of typical intercalation compounds, the electrochemical performance of MXene electrodes is strongly influenced by the presence of co‐inserted solvent molecules, which cannot be detected by conventional current/potential electrochemical measurements. Furthermore, the electrochemical insertion of ions into MXene interspaces results in strong coupling with the intercalation‐induced structural, dimensional, and viscoelastic changes in the polarized MXene electrodes. To shed light on the charging mechanisms of MXene systems and their associated phenomena, the use of a large variety of real‐time monitoring techniques has been proposed in recent years. This review summarizes the most essential findings related to the charging mechanism of Ti3 C2 T x electrodes and their potential induced structural and mechanical phenomena obtained by in situ investigations. Abstract : MXene compounds and particularly Ti3 C2 T x are considered to be promising candidates for energy storage. The 2D structure and the surface chemistry of the MXene result in chemical, physical and mechanical variations during their charging/discharging processes. This review provides a comprehensive summary of the major findings obtained by in situ investigations of MXene electrodes and proposed future directions for investigations of MXene structures.